"I'd trust them if they understood learning disabilities" support needs of people with learning disabilities in the Criminal Justice System. (9th March 2015) - Howard, Ruth; Phipps, Emma; Clarbour, Jane; Rayner, Kelly
Abstract : Purpose: – People with learning disabilities (LD) often lack necessary support in navigating and coping within the Criminal Justice System (CJS). The purpose of this paper is to explore their experiences, from their own perspective, and identify the supports which need to be implemented. Design/methodology/approach: – Focus groups were held with nine patients in a forensic LD service, discussing their experiences and support needs within the CJS. Template analysis was undertaken on the transcripts. Findings: – Four themes were identified: negative feelings, professional attitudes, suitability of the CJS, and supports needed. Practical implications: – This research demonstrates the valuable opinions to be obtained from offenders with LD on their experiences and needs. Implications for the CJS include a need for further awareness, training, and expertise to work effectively with people with LD. Participant perspectives also highlight the importance of consistent liaison and diversion schemes, and indicate that CJS services may have something to learn from healthcare settings. Originality/value: – Previous knowledge of offenders with LD overlooked the perspective of the service user. This research has given this group a voice, and has benefited from their insight. This is a timely piece of research in the current landscape of the CJS, and so these findings may be of practical value to the implementation of supports, particularly the liaison and diversion schemes.